Case Report: Accelerated parathyroid adenoma progression and hypercalcemia-driven neurotoxicity following pembrolizumab-based neoadjuvant therapy in triple-negative breast cancer: a case of multisystem immune-related adverse events - Zeng, Yi; Sun, Yu; Qian, Pengfei (Frontiers in Oncology, 2025)
This case report describes a 45-year-old TNBC patient (cT3N1M0 IIIA) with preexisting parathyroid adenoma who developed multisystem immune-related toxicities after neoadjuvant pembrolizumab chemotherapy. After two cycles, severe hepatotoxicity (ALT 1,090 U/L), grade 2 dermatitis, hypercalcemic crisis (iPTH 61.99 pmol/L), and meningeal thickening with intracranial hypertension emerged. Imaging revealed 134% parathyroid adenoma enlargement and diffuse meningeal enhancement. Emergency parathyroidectomy and corticosteroids normalized calcium and reversed neurological symptoms. Pathological complete response (pCR) occurred despite ICI discontinuation. This first-reported case suggests that PD-1 inhibitors may activate parathyroid microenvironments to drive adenoma growth. At the same time, calcium–ICI synergy could impair blood–brain barrier integrity, advocating calcium/neurological monitoring in ICI-treated endocrine disorder patients.